Transmisión altomedieval de una receta ad uermes in homine aut in caballo - Santamaría Hernández, María Teresa (Pallas, 2016)
In this article we analyze the transmission of a prescription ad uermes in homine aut in caballo in three medicinal compilations from Early Middle Ages. So far the prescription has only been found in one of them, the Receptarium Laureshamense. This analysis and the comparison of the chapters that provide the prescription appear to allow us to interpret the disease for which it is indicated (uermes), which falls within the scope of Veterinary Medicine and has nothing to do with the lumbrici. In addition, we provide new data for a possible identification of the plant that is used in the prescription, called cromella.